Structural Deviation in the Poetry of Samir Al-Omari - یداللهي فارساني, عباس (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The phenomenon of deviation is considered as one of the structural aspects of texts which deals with poetical discourse and unveils the artistic strength of the contemporary poets. Deviation is highly important in revealing the linguistic power of poets in expressing deep implications and role of the readers in understanding different implications. The present study is an attempt to investigate and analyze the structural deviation in the poetry of Samir Al-Omari who is one of the innovative poets in the field of contemporary poetry of Palestine. He has made efforts to advocate the topic of Palestine and to condemn the criminal actions of the Zionist regime. This study has been conducted based on an analytico-descriptive method as well as relying on the resources that have helped us to do so. In the end, the research came to this conclusion that the poet has used this expressive technique to reveal his internal thoughts and feelings among which the topic of Palestine is central. In addition, he tries to use this technique to add a kind of semantic variety and aesthetic feature to the contemporary ode. Among the most important structural deviations in his poetry, one can refer to post position, delay, omission, variety for attention, repetition, and structural separation.